2022
DOI: 10.3390/microorganisms10112129
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetics and Microbiota Interactions in Colorectal Cancer: Shared or Independent Risk?

Abstract: The role of microbiota in colorectal cancer has been studied since alterations in its composition were observed. In addition, there are more and more pieces of evidence that microbiota could be implicated in colorectal cancer progression. Thus, the components of the microbiota could be biomarkers for the diagnosis and prognosis of colorectal cancer. In addition, it is important to address how the microbiota interacts with the host and how the host shapes the microbiota, in order to understand the biological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…In addition, LASSO regression analysis led to the generation of a risk scoring model for EC, incorporating the Nitriliruptor microbiome. Previous research has linked Nitriliruptor to colorectal cancer (CRC), revealing a strong correlation between Nitriliruptor abundance and the expression of host genes in advanced-stage CRC [ 23 , 24 ]. Moreover, a forest plot derived from univariate COX regression analysis demonstrated that a higher abundance of Blautia bacteria correlated with a poorer clinical prognosis in EC patients (HR, 3.923; 95% CI: 1.505–10.225; P = 0.019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LASSO regression analysis led to the generation of a risk scoring model for EC, incorporating the Nitriliruptor microbiome. Previous research has linked Nitriliruptor to colorectal cancer (CRC), revealing a strong correlation between Nitriliruptor abundance and the expression of host genes in advanced-stage CRC [ 23 , 24 ]. Moreover, a forest plot derived from univariate COX regression analysis demonstrated that a higher abundance of Blautia bacteria correlated with a poorer clinical prognosis in EC patients (HR, 3.923; 95% CI: 1.505–10.225; P = 0.019).…”
Section: Discussionmentioning
confidence: 99%
“…S. bovis and its subclasses, types I and II, have been linked to endocarditis, colorectal carcinoma, and biliary tract illnesses [ 10 , 75 , 78 , 79 ]. The relationship between S. bovis and colorectal carcinoma has been well acknowledged recently, mainly including S. gallolyticus bacteria [ 10 , 37 , 71 , 75 , 79 , 80 ]. However, whether the bacteria causes colon cancer or the cancerous lesions cause favorable conditions and a conduit for bacteria to multiply and enter the blood circulation is ambiguous [ 79 ].…”
Section: Reviewmentioning
confidence: 99%
“…In 2015, Glibetic et al [ 79 ] proposed that S. bovis is a driver and a passenger cancer microorganism [ 79 , 80 ]. This microbiota is a contributory element that expedites the development of CRC [ 10 , 37 , 71 , 79 , 80 ]. In the presence of S. bovis septicemia, there was a seven-fold increase in the possibility of having CRC, as reported in the study [ 9 , 75 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations